Diversity of parasitoid fauna of the leafminer fly, Lirlomyza huidobrensis (Diptero: Agromyzidae) on beans in the Lima area of Perú - LANNACONE-OLIVER, JOSÉ ALBERTO (Revista Colombiana de Entomología, 1998)
In the area of Lima, Perú, the diversity of parasitoids fauna of the leafminer fly Liriomyza huidobrensis (Blanchard) that affect bean crop variety "Canario" were assessed with the Shannon Weiner index (H’) every ten days from October to December in one ha of the crop. The field was divided into five areas, in each one was sampled ten plants, collecting one hundred leaves of the middle and lower parí of the plants. The number of emerging adults fly. parasitoids and empty puparia were sampled at the laboratory. The number of miner leaves during the evaluation was 52,37% with a variation from 26 to 76%. The parasitoids recovered in order of importance were Halticoptera arduine Walker (Pteromalidae) (60,13%), Diglyphus ivebsteri (Crawford) (Eulophidae)(29,41%), Chrysocharis phytoyzae (Bre.)(Eulophidae) (8,49%) and Ganaspidium sp. (Cynipidae) (1,97%). The dominant specie was the endoparasitic Halticoptera for all the sampling and for the end of the crop, the ectoparasitic Diglyphu.v was dominant. The diversity Shannon Weiner average value for the parasitoids microwaps was H’=0,26. The Simpson index D=0,14 and the value E= 0,56. The percentage of parasitism was 33,33% and with a variation from O — 57,13%. The value three was the more frequent number of parasitoids during a half percent of all assesses. The Spearman’s correlation matrix showed a positive relation between 1-1". Djinn the number of parasitoids species. In addition to formerly, the number of endoparasitoids and ectoparasitoids of the leafminer fly in bean crop was statistical the same. The parasitoids recovered in fields without insecticides and their correspondent liberation permit the best use of the benefit fauna for the population control of L. huidobrensis.